A prospective evaluation of the inoculation of homogenised tissue and bone biopsies in blood culture bottles for the diagnosis of orthopaedic-device-related infections - A.-S. Jacob; J. Onsea; J. Onsea; L. Bessems; L. Bessems; P. Spoormans; G. Vles; W.-J. Metsemakers; W.-J. Metsemakers; S. Ombelet; M. Depypere (Journal of Bone and Joint Infection)
Fracture-related infections (FRIs) and periprosthetic joint infections (PJIs) occur in nearly 2 % of patients with orthopaedic devices, contributing to significant morbidity and mortality. Effective microbiological diagnosis of these infections remains challenging, with the homogenisation of bone/tissue biopsies recognised as the most reliable pre-analytical procedure.